Site and provenance interact to influence seasonal diameter growth of Pseudotsuga menziesii - Harrington, Constance A.; Gould, Peter J.; Cronn, Richard (Frontiers in Forests and Global Change, 2023)
Phenology of diameter growth in trees has been studied for many years but generally using a limited number of sites and genotypes. In this project provenances of Douglas-fir (Pseudotsuga menziesii var. menziesii) planted across a wide range of environments were used to evaluate diameter growth and phenology to an extreme heat event and to seasonal conditions. Sampling was done in nine common gardens in western Oregon and Washington, USA that included a coastal site, a low elevation interior site, and high elevation interior site on three latitude bands. In 2021, three provenances at four sites were monitored for late-season diameter growth following an extreme heat event in June. In 2022, five provenances were evaluated for full-seasonal diameter growth at four growth intervals across all nine sites. Growth after the 2021 extreme heat event varied by planting site, with the greatest growth observed at mild (cooler/wetter) sites and the least growth observed at arid (hotter/drier) sites. Comparisons of diameter growth over the late season period (i.e., July–October) showed that 2022 growth was 1.25-fold to 3.70-fold higher, presumably due to premature growth cessation in 2021. In 2022, diameter growth rates showed significant variation by site and provenance; the interaction between site and provenance was significant in all but the first growth interval. Intra-seasonal growth rates were not consistent across sites; there was substantial diameter growth early in the season on sites with continental climates, little diameter growth by any provenance after early August at three high elevation sites, and most sources continued growth later in the season at coastal sites. One source differed more in phenology across sites than the others, apparently due to its susceptibility to a needle-cast disease. Cambial phenology varied with genetic and site factors that control the timing of growth and intrinsic growth rates. In addition, the interaction between genotype and site resulted in some provenances performing better than others on some sites as a function of disease susceptibility or response to environmental factors. Understanding phenology of seed sources under a range of site conditions should help predict diameter growth under different climate conditions in the future.